The Effect of Giving Coffee Pulp Extract Cream on the Healing of Cut Wounds in Wistar Rats - Anggun Juita; Refi Ikhtiari; Erny Tandanu; Reghita Claudia Malau (CV. Inara, 2025)
Humans need skin to protect their internal organs, such as muscles, nerves, and bones, from disease. This study examines the effect of coffee grounds extract cream on wound healing in Wistar rats. This study is an experimental laboratory study. The research design used a post-test with a control group design or control on samples based on treatment groups to analyze the effect of coffee grounds extract on wound healing and skin histopathology in male Wistar white rats. According to the results of the study, coffee grounds extract accelerated wound healing in Wistar white rats, as shown by the average differences of 2.5%, 5%, and 10%. This study shows that coffee grounds extract contains saponins, alkaloids, flavonoids, and tannins. Research on skin histopathology on the best fibroblast tissue found that 10% coffee grounds extract cream was the most helpful in developing connective tissue in injured skin. The findings of this study are expected to help other researchers explore the effects of coffee grounds extract on skin collagen formation.